Assessing quantitatively charge carrier fate in 4-chlorophenol photocatalytic degradation using globular titania catalysts: Implications in quantum efficiency calculation. Issue 5 (October 2021) - Caudillo-Flores, Uriel; Avilés-García, Osmín; Alonso-Núñez, Gabriel; Kubacka, Anna; Fernández-García, Marcos
Abstract: The complex interplay between photons and catalytic powders in liquid-phase photocatalytic degradation reactions requires combined computational and experimental approaches to render a quantitative assessment of the light harvesting and handling properties the system. The full assessment of the light-to-chemical efficiency is here presented for the first of time for the complex 4-chlorophenol degradation. The reaction is carried out under different illumination conditions (UV, visible) with advanced, globular titania catalysts displaying high activity with respect to P25 and other reference materials. A critical issue, up to know not accounted for in the literature, is the effect that the different reaction products exerts in the use of charge carrier species by the catalytic system. Quantifying light effects in chemical conversion with explicit analysis of kinetically-relevant charge carrier species fate drives to correction(s) of the quantum efficiency observable, with a magnitude up to ca. 100%. The work outlines a novel and general procedure for the quantitative assessment of the real number of photons used in transforming pollutants through any liquid-phase photocatalytic process. Graphical Abstract: ga1 Highlights: UV and visible degradation of 4-chlorophenol using globular titania. Activity analysis through quantum efficiency and real photon use by the catalysts. Introduction of chemical effects in liquid-phase degradation efficiency calculations. Quantitative assessment of photoactivity. Optimized globular titania improves the performance of P25 under all illuminations.